MENGANALISIS PERAN OCB DALAM HUBUNGAN WORK LIFE BALANCE DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GENERASI Z - Lailatur Rizki, Via; Abrori, Imam; Muttaqien, Fauzan (Universitas Bina Taruna Gorontalo, 2025)
This study aims to determine and analyze the effect of work life balance, emotional intelligence through OCB on generation Z performance with a case study of banking employees in the Lumajang area, East Java. This research uses quantitative methods by distributing questionnaires to respondents, namely generation Z who work in banking in Lumajang, through a sampling method, namely purposive sampling and there are 45 respondents. The analysis method in this study uses path analysis with the results of work life balance and emotional intelligence affecting OCB, work life balance and emotional intelligence affecting employee performance, emotional intelligence affecting employee performance, OCB affecting employee performance, and work life balance and emotional intelligence affecting employee performance through OCB.